Numerical Shear Tests on the Scale Effect of Rock Joints under CNL and CND Conditions - Xige Liu; Wancheng Zhu; Lankun Li (Advances in Civil Engineering)
The scale effect of rock joint shear behavior is an important subject in the field of rock mechanics. There is yet a lack of consensus regarding whether the shear strength of rock joints increases, decreases, or remains unchanged as the joint size increases. To explore this issue, a series of repeated and enlarged numerical joint models were established in this study using the particle flow code (PFC2D). The microparameters were calibrated by uniaxial compression tests and shear tests on the concrete material under the constant normal loading (CNL) condition. Three different normal stresses were adopted in numerical shear tests with joint specimen lengths ranging from 100 mm to 800 mm. In addition to the commonly used CNL, the constant normal displacement (CND) condition was established for the purposes of this study; the CND can be considered an extreme case of the constant normal stiffness (CNS) condition. The shear stress-shear displacement curves changed from brittle failure to ductile failure alongside a gradual decrease in peak shear strength as joint length increased. That is, an overall negative scale effect was observed. Positive scale effect or no scale effect is also possible within a limited joint length range. A positive correlation was also observed between the peak shear displacement and joint length, and a negative correlation between shear stiffness and joint length. These above statements are applicable to both repeated and enlarged joints under either CNL or CND conditions. When the normal stress is sufficiently high and shear dilatancy displacement is very small, the shear behavior of rock joints under CNL and CND conditions seems to be consistent. However, for shear tests under low initial normal stress, the peak shear strength achieved under the CND condition is much higher than that under the CNL condition, as the normal stresses of enlarged joints increase to greater extent than the repeated ones during shearing.